The Overview Side Effects of MDR TB Short Term Regimen for Heart and Kidney Function in MDR TB Patients at H. Adam Malik General Hospital Medan, North Sumatra - Santy, Diana; Siagian, Parluhutan; Sinaga, Bintang YM; Eyanoer, Putri C (Jurnal Respirologi Indonesia, 2024)
Background: World Health Organization issued a recommendation for the use of standard 9–11 month Shorter Multidrug-Drug Resistant Tuberculosis (MDR TB) regimen. It will impact the number of patients treated and improve obedience because of the shorter, low cost, and well-tolerated. However, MDR TB drugs allow side effects both mild, moderate and severe. If severe side effects occur, the patient will stop treatment and close monitoring required. An optimal and adequate care of side effects is the key of the successful of MDR TB treatment. The aim of this study was to determine the side effects that occured in the treatment of MDR TB patients with short term regimen (STR) on heart and kidney function at H. Adam Malik General Hospital Medan, North Sumatra.Methods: A case series design with a total of 76 MDR TB patients who underwent a shorter regimen. Samples were obtained from the medical record in the pulmonary isolation inward and MDR TB polyclinic at Adam Malik Hospital, Indonesia. Data were analyzed descriptively to identify changes in heart (Prolong QTc) and kidney function of the nine months treatment.Results: 76 data were collected, the number of male samples was 68.4% and 31.6% were women with the age group of the study subjects being mostly followed by 41-50 years of age. There was a significant increase in value occurred in 4-6 months of treatment related to the side effects of treatment on heart (Prolong QTc) and kidney function.Conclusion: There was a trend to increase the value of heart (Prolong QTc) and kidney function significantly occurred 4-6 months after the patient underwent MDR TB treatment with STR.